CORPORATE PRODUCTION AND FINANCING CHOICES IN HUNGARY - Katona, Klára (Ekonomika, 2014)
The objective of this study is to investigate how Hungarian firms could finance their production in the circumstances of the Hungarian financial market, including economic policy and credit supply in the last two decades. We put the question whether the companies could effectively use the sources which owners and creditors provided for them. The growing proportion of the debt in firms’ capital may have positive – not only negative – effects on companies at the same time, which forces the owners and managers to replace the shareholders’ equity with credits. However, the availability of credits depends on the solvency of firms on the one hand and the development of the financial market on the other hand.The study analyses the capital structure of firms in Hungary by financial indicators and their productivity in a regression model. We review the effects of the Hungarian economic policy and credit supply on financing choices and the performance of the corporates.The database of Hungarian enterprises represents nearly 90% of firms in the country. We differentiate among the companies according to their ownership and size. The period includes 18 years between 1992 and 2009. The records contain all relevant information from annual reports, e.g., balance sheets, profit and loss figures.